Promoting family- centred early interventions: evaluating predictors of early paternal involvement for children with disabilities in the United Arab Emirates - Ahmed Mohamed; Maxwell Peprah Opoku; Laurent Gabriel Ndijuye; Shamsa Almarzooqi; Ebenezer Mensah Gyimah (International Journal of Adolescence and Youth)
Debates on paternal engagement in caregiving for children with disabilities in the early years of development has been limited in non-Western contexts. The current study drew on mothers and fathers to understand paternal involvement in the provision of early intervention services to children with disabilities in the United Arab Emirates. We administered the Fathers’ Involvement in Disability Rehabilitation Scale to 598 couples. We analysed data using multivariate analysis of variance, hierarchical multiple regression, and moderation. The findings indicated positive ratings for attitude and support towards children with disabilities; however, responses regarding training were ambivalent. Furthermore, there was a significant correlation between the three domains of involvement: attitude, support, and training. Parent type did not moderate the relationship between demographics and the two domains – attitude and participation in training. The findings underscore the need for paternal training and engagement to enhance the early development of children with disabilities.